1991
DOI: 10.1071/zo9910499
|View full text |Cite
|
Sign up to set email alerts
|

Population Biology of Euperipatoides-Leuckartii (Onychophora, Peripatopsidae)

Abstract: This paper reports on a population study of the onychophoran Euperipatoides leuckartii. The species was found to be extremely abundant in decomposing logs from the Tallaganda State Forest area. Analysis of its distribution indicated that E. leuckartii occurred only in logs with a relative water content greater than 211 %. Furthermore, the occurrence of E. leuckartii was found to be congruent with that of termites. Abundance was also correlated with altitude, which suggests an effect of tree species, although o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
79
2
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(87 citation statements)
references
References 0 publications
5
79
2
1
Order By: Relevance
“…They retain this position in the adult gonad, the lumen of which is a derivative of the embryonic coelomic cavities, and develop into the spermatogonia of the testes and the oogonia of the ovaries (Ruhberg and Storch 1976 ;Herzberg et al 1980 ;Storch and Ruhberg 1990 ;Huebner and Lococo 1994 ;Storch et al 1995 ;Brockmann et al 1999Brockmann et al , 2001Mayer and Tait 2009 ). Irrespective of the ovarian type (exogenous versus endogenous), the ovarian anlage initially shows a sterile dorsal and a germinal ventral portion, the latter containing the presumptive oogonia Scott and Rowell ( 1991 ), Reid ( 1996 ), Curach and Sunnucks ( 1999 ), Barclay et al ( 2000a , b ), Clarke and Spier-Ashcroft ( 2001 ), Sunnucks and Tait ( 2001 ), Reinhard and Rowell ( 2005 ) (Fig. 4.14C-E ).…”
Section: Euperipatoides Rowelli : An Emerging Model For Developmentalmentioning
confidence: 90%
“…They retain this position in the adult gonad, the lumen of which is a derivative of the embryonic coelomic cavities, and develop into the spermatogonia of the testes and the oogonia of the ovaries (Ruhberg and Storch 1976 ;Herzberg et al 1980 ;Storch and Ruhberg 1990 ;Huebner and Lococo 1994 ;Storch et al 1995 ;Brockmann et al 1999Brockmann et al , 2001Mayer and Tait 2009 ). Irrespective of the ovarian type (exogenous versus endogenous), the ovarian anlage initially shows a sterile dorsal and a germinal ventral portion, the latter containing the presumptive oogonia Scott and Rowell ( 1991 ), Reid ( 1996 ), Curach and Sunnucks ( 1999 ), Barclay et al ( 2000a , b ), Clarke and Spier-Ashcroft ( 2001 ), Sunnucks and Tait ( 2001 ), Reinhard and Rowell ( 2005 ) (Fig. 4.14C-E ).…”
Section: Euperipatoides Rowelli : An Emerging Model For Developmentalmentioning
confidence: 90%
“…Susceptibility to desiccation, resulting from the absence of a waterproof integument and the presence of unclosable tracheal spiracles (Wright & Luke, 1989;Lavallard & Campiglia-Reimann, 1966;Pereira, Bicudo & Campiglia, 1985), seems to dictate microhabitat choice (Newlands & Ruhberg, 1978). In drier forests, Onychophora aggregate in moist decaying logs and leaf litter (Ruhberg, 1985;Scott & Rowell, 1991;New, 1995). Indeed, when Scott & Rowell (1991) examined the role of a number of habitat variables in determining the suitability of an area for Euperipatoides rowelli Reid 1996 in Tallaganda State Forest, New South Wales, they concluded that the water content of decomposing logs was the principal determinant of log suitability.…”
Section: Introductionmentioning
confidence: 97%
“…Due to their low vagility and strict microhabitat requirements, it has been suggested that onychophorans may be predisposed to inbreeding (Monge-Najera, 1995;Scott & Rowell, 1991;Rowell et al, 1995); however, this has not been addressed in ®eld studies.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The Peripatopsidae include oviparous and ovoviviparous species, and some authors state that there are species in this family exhibiting nonplacental or primitive vivipary (Anderson, 1973;Ruhberg, 1985Ruhberg, , 1990Scott & Rowell, 1991). Since no placenta or maternal connection has been seen in any peripatopsid uterus, Ghiselin (1984) suggests that embryos may receive nourishment from the mother in the form of secretions.…”
Section: Introductionmentioning
confidence: 96%